2014
DOI: 10.3906/sag-1208-13
|View full text |Cite
|
Sign up to set email alerts
|

Normal M mode values in healthy Turkish children

Abstract: Evaluation of cardiac structures requires a large study group for accurate data on normal values. The aim of the study was to obtain normal M mode echocardiographic values in a substantial sample of healthy term neonates and children to develop centile charts.Materials and methods: Data were obtained over 2 years from a single center in Turkey, from 1200 healthy infants and children aged 1 day to 17 years. Using echocardiographic investigation, measurements were obtained of the following: left ventricular dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Moreover, the reported range of the atrial maximal and minimal volume index values [51] matches with the simulated left and right atrial maximal and minimal volume indexes in the healthy child cardiovascular system for 1 m 2 body surface area. Typically, the left ventricular end-diastolic and end-systolic diameters are around 4.1 cm and 2.6 cm, the right ventricular basal diameter at the end of the diastole is around 2 cm and the left atrial maximal diameter 2.9 cm and changing again within a physiologic variation range for the studied age interval [6971]. The simulated dimensions in the cardiac chambers remain within the physiologic range and match with the reported values in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reported range of the atrial maximal and minimal volume index values [51] matches with the simulated left and right atrial maximal and minimal volume indexes in the healthy child cardiovascular system for 1 m 2 body surface area. Typically, the left ventricular end-diastolic and end-systolic diameters are around 4.1 cm and 2.6 cm, the right ventricular basal diameter at the end of the diastole is around 2 cm and the left atrial maximal diameter 2.9 cm and changing again within a physiologic variation range for the studied age interval [6971]. The simulated dimensions in the cardiac chambers remain within the physiologic range and match with the reported values in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no consensus exists as to which growth parameter is most appropriate in standardizing cardiac measures for children [15] . Different parameters have been used in the published references, including height [16] , weight [3] , BSA [2] , [4] , lean body mass [17] , [18] and age [19] , [20] , [21] . Roge et al showed that height, weight and BSA were strongly correlated, resulting in similar regression equations using either of the parameters [22] .…”
Section: Discussionmentioning
confidence: 99%
“…As cardiac chamber dimensions can change with somatic growth in childhood and adolescence, it is important to normalise echocardiographic measurements to body size. Several echocardiographic references have been published for children and adolescents from various regions including Europe, Asia and North America [1] , [2] , [3] , [4] , [5] . However, no echocardiography references have been established for children and adolescents in sub Saharan Africa, and echocardiographic studies from this region have utilised published references for normative data mostly derived from predominantly white populations [4] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…One study used three-dimensional (3D) echocardiography in addition to M-mode and 2D, another utilised 3D only and a third study used a rarely practiced echocardiographic technique called acoustic quantification [ 18 , 21 , 22 ]. Anthropometric and non-anthropometric measures were used for normalising the results: body surface area (BSA) in 18 studies, height ( n = 4) [ 8 , 11 , 17 , 28 ], weight ( n = 3) [ 10 , 20 , 35 ], age ( n = 2) [ 14 , 15 ], and lean body mass ( n = 1) [ 7 ]. The remaining studies used age and heart rate, ( n = 1); [ 22 ] age and BSA, ( n = 2); [ 26 , 37 ] age and height, ( n = 1); [ 27 ] height and BSA, ( n = 1); [ 33 ] weight and BSA, ( n = 1) [ 36 ] and one study used height, BSA and lean body mass [ 25 ].…”
Section: Resultsmentioning
confidence: 99%